IMPLEMENTASI PERTANIAN CERDAS BERBASIS IOT PADA KELOMPOK TANI TEGER 02 DESA MANGUNSARI: Implementation of IoT-Based Smart Farming in the TEGER 02 Farmer Group in Mangunsari Village - Anan Nugroho; Feddy Setio Pribadi; Mona Subagja; Syahroni Hidayat; Ahmad Zein Al Wafi; Muhammad Fathurrahman; Zidan Vieri Wijaya; Agus Ardiyanto; Haikal Abror (Jurnal Abdi Insani, 2023)
Plantation is a very important sector to meet food needs in Indonesia. However, plantations in Indonesia do not always increase over time. There are still many plantation sectors whose productivity is still low, especially in rural areas. Factors such as lack of capital and technology, lack of market access, and social problems such as land conflicts often become obstacles to the development of a productive and sustainable plantation sector. One example of a farmer group experiencing problems in water distribution is the TEGER 02 farmer group in Mangunsari Village, Semarang City, Central Java. This group has 7 hectares of land and 20 workers. However, the biggest obstacle faced is ineffective water distribution, especially during the dry season. Currently, to water 3000 ð‘š2 of cultivated land, the group needs a full day involving 3 workers. Of course, the ratio between a few workers and a large area of land is inversely proportional, so it takes workers a long time to water the plantation land. To overcome this problem, a tool has been developed that can help farmers distribute water that utilizes strong internet access, the Internet of Things (IoT). IoT is very suitable to be applied to Mangunsari Village plantations. An IoT-based sprinkler that can help farmers in watering automatically which is connected to a website application so that it can be accessed directly using the farmer's smartphone. As an electricity supply, photovoltaics are used as an environmentally friendly energy source with a conservation perspective. The results of the service show that this activity makes it very easy for farmers to overcome watering problems which are difficult to control because the number of workers is not proportional to the size of the plantation land. However, adjustments to the website need to be made to produce an application that is more responsive when accessed via farmers' smartphones.